Jezebel - Davis, Owen 1874-1956; Steiner, Max 1888-1971 (Warner Bros. Entertainment Inc., 2019)
"Jezebel" (1938) is a romantic melodrama with views of early 1850s New Orleans ante-bellum society. It was the first in a cycle of films with Dixie backdrops that studied Southern chivalry and honor. The role of the title character was offered as compensation to film star Bette Davis - her first major film role - when she lost the opportunity to play Scarlett O'Hara in "Gone with the Wind" (1939), a characterization with a similar heroine. In fact, the film has been called a black-and-white version of the famous Selznick film that was in its pre-production stages. Director William Wyler and Warner Bros' Studios brilliantly fashioned the superb character study with superior production values. [www.filmsite.org]
Orig.: USA, 1938
Special features: Commentary by Film Historian Jeanine Basinger; Featurette: Jezebel: Legend of the South; Vintage Musical Short Melody Masters: Jimmy Dorsey and His Orchestra; Classic Cartoon Daffy Duck in Hollywood; Promotion: Rambling 'round the Hollywood Studio with the Candid Cameraman; Theatrical Trailer
Keywords: Romance; Melodramas; Melodrama; Liebesfilm; Blu-Ray-Disc; DVD-Video